The Structure of the Cobalt Oxide/Au Catalyst Interface in Electrochemical Water Splitting. Issue 37 (7th August 2018) - Fester, Jakob; Makoveev, Anton; Grumelli, Doris; Gutzler, Rico; Sun, Zhaozong; Rodríguez‐Fernández, Jonathan; Kern, Klaus; Lauritsen, Jeppe V.
Abstract: The catalytic synergy between cobalt oxide and gold leads to strong promotion of the oxygen evolution reaction (OER)—one half‐reaction of electrochemical water splitting. However, the mechanism behind the enhancement effect is still not understood, in part due to a missing structural model of the active interface. Using a novel interplay of cyclic voltammetry (CV) for electrochemistry integrated with scanning tunneling microscopy (STM) and X‐ray photoelectron spectroscopy (XPS) on an atomically defined cobalt oxide/Au(111) system, we reveal here that the supporting gold substrate uniquely favors a flexible cobalt‐oxyhydroxide/Au interface in the electrochemically active potential window and thus suppresses the formation of less active bulk cobalt oxide morphologies. The findings substantiate why optimum catalytic synergy is obtained for oxide coverages on gold close to or below one monolayer, and provide the first morphological description of the active phase during electrocatalysis. Abstract : One half‐reaction of electrochemical water splitting is the oxygen evolution reaction, which is promoted by the catalytic synergy between cobalt oxide and gold. The mechanism behind that enhancement effect is still not understood. It is revealed that the supporting gold substrate uniquely favors a flexible cobalt‐oxyhydroxide/Au interface in the electrochemically active potential window and thus suppresses the formation of less active bulk cobalt oxide morphologies.